Experimental Study of Polymer Concrete Material with SBR Latex for Bridge Pier: Compressive Test, Tensile Test, and Workability on Cylinder and Steel Samples - Justitiannisa, Innino; Gunadi, Riawan (Fakultas Teknik Universitas Tanjungpura, 2025)
Concrete is a fundamental material in civil engineering structures due to its high compressive strength and durability. However, its low tensile strength, high permeability, and tendency to crack under environmental and mechanical stress limit its long-term performance, especially in substructures such as bridge piers exposed to dynamic and aggressive conditions. This study investigates the effect of incorporating 10% Styrene-Butadiene Rubber (SBR) Latex by weight into a polymer-modified concrete mix. The objective is to evaluate its mechanical behavior and workability as a preliminary step toward application in full-scale bridge pier construction. The concrete was designed using the Ohama method, which considers the interaction between polymer content and water